Electrospraying of microfluidic encapsulated cells for the fabrication of cell-laden electrospun hybrid tissue constructs. (December 2017) - Weidenbacher, L.; Abrishamkar, A.; Rottmar, M.; Guex, A.G.; Maniura-Weber, K.; deMello, A.J.; Ferguson, S.J.; Rossi, R.M.; Fortunato, G.
Graphical abstract: Abstract: The fabrication of functional 3D tissues is a major goal in tissue engineering. While electrospinning is a promising technique to manufacture a structure mimicking the extracellular matrix, cell infiltration into electrospun scaffolds remains challenging. The robust and in situ delivery of cells into such biomimetic scaffolds would potentially enable the design of tissue engineered constructs with spatial control over cellular distribution but often solvents employed in the spinning process are problematic due to their high cytotoxicity. Herein, microfluidic cell encapsulation is used to establish a temporary protection vehicle for the in situ delivery of cells for the development of a fibrous, cell-laden hybrid biograft. Therefore a layer-by-layer process is used by alternating fiber electrospinning and cell spraying procedures. Both encapsulation and subsequent electrospraying of capsules has no negative effect on the viability and myogenic differentiation of murine myoblast cells. Propidium iodide positive stained cells were analyzed to quantify the amount of dead cells and the presence of myosin heavy chain positive cells after the processes was shown. Furthermore, encapsulation successfully protects cells from cytotoxic solvents (such as dimethylformamide) during in situ delivery of the cells into electrospun poly(vinylidene fluoride-co-hexafluoropropylene) scaffolds. The resulting cell-populated biografts demonstrate the clear potential of this approach in the creation of viable tissue engineering constructs. Statement of Significance: Infiltration of cells and their controlled spatial distribution within fibrous electrospun membranes is a challenging task but allows for the development of functional highly organized 3D hybrid tissues. Combining polymer electrospinning and cell electrospraying in a layer-by-layer approach is expected to overcome current limitations of reduced cell infiltration after traditional static seeding. However, organic solvents, used during the electrospinning process, impede often major issues due to their high cytotoxicity. Utilizing microfluidic encapsulation as a mean to embed cells within a protective polymer casing enables the controlled deposition of viable cells without interfering with the cellular phenotype. The presented techniques allow for novel cell manipulation approaches being significant for enhanced 3D tissue engineering based on its versatility in terms of material and cell selection.